Analisis Pengaruh Aspek Hukum, Peran Bidan Dan Hak Anak Terhadap Praktik Pemberian ASI Eksklusif Di Kabupaten Klaten - Sumantri Sumantri; Gita Kostania (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: Legal Aspects, The Role Of Midwife, The Rights Of Children, Exclusive Breastfeeding. The purpose of this study is to analyze the influence of the legal aspects, the role of the midwife and the right of children on exclusive breastfeeding practice. This type of research is an analytical study with cross-sectional research design. An estimated 1,000 Mothers with infants aged 0-12 months in the Klaten district with 30% of the sample population, it’s about 300 people. The sampling technique used cluster random sampling. Analysis of the data used by the statistical test Chi-Square and logistic regression. Results: 1) legal aspect of regulation Exclusive Breastfeeding is significantly affect the exclusive breastfeeding practice, p 0.000 (P <0.05); X2: 23.5; RP: 1.80 and 95% CI: 1:40 to 2:31; 2) the role of the midwife in exclusive breastfeeding practice showed a significant effect, p 0.001 (P <0.05); X2: 11.9; RP: 1:52 and 95% CI: 1.22-1.89, and; 3) the right of the child to exclusive breastfeeding practice showed a significant effect, p 0.000 (P <0.05); X2: 32.3; RP: 2:07 and 95% CI: 1.55-2.66.